RISK FACTORS OF HYPERTENSION IN PREGNANT WOMEN IN LABUHANBATU REGENCY: A CROSS−SECTIONAL STUDY: Faktor Risiko Hipertensi Pada Ibu Hamil di Kabupaten Labuhanbatu - Hartono, Hartono; Manalu, Putranto; Janas, Dhyta Nurhasanah; Siagian, Masryna; Nadapdap, Marshall Jeremia (Jurnal Berkala Epidemiologi, 2025)
Background: Pregnant women with hypertension face elevated risks of complications, including preeclampsia and maternal mortality. Despite the increasing prevalence of gestational hypertension and its associated burdens, limited research—particularly at the local level—hinders effective prevention and management strategies. Purpose: This research aimed to investigate the risk factors associated with hypertension in pregnant women in Labuhan Batu Regency. Methods: This cross-sectional study involved 80 pregnant women from Labuhanbatu Regency, North Sumatra, Indonesia. Data on obesity, age, physical activity, and secondhand smoke exposure were collected through measurements and questionnaires. Obesity was assessed using mid-upper arm circumference (MUAC), while other variables were determined through interviews. Data were analyzed descriptively, and Fisher’s exact test was employed to compare risk factors between hypertensive and non-hypertensive pregnant women. Results: Obesity (p=0.29) and age (p=0.84) were not significantly associated with hypertension. However, pregnant women with light physical activity had a lower risk of hypertension compared to those with heavy physical activity (p=0.02). There was no significant association between exposure to cigarette smoke and hypertension (p=0.20). Conclusion: The findings suggest that light physical activity might be protective against hypertension during pregnancy among homemakers in Labuhanbatu regency.